Areopagitica, or the Uses of Literacy according to John Milton - Pierre Lurbe (Revue LISA)
John Milton’s plea For the Liberty of Unlicens’d Printing, Areopagitica, is now hailed as “a landmark argument against censorship” (S. B. Dobransky). Yet the book passed unnoticed when it was first published, and the range of opinions that Milton was prepared to tolerate remained strictly circumscribed: Roman Catholics, as well as all those who professed impiety or disregarded common morality, had no right to be tolerated in print. Yet the inner logic of Milton’s own argument propels Areopagitica well beyond the confines of its self-proclaimed limitations. Milton launches into a celebration of the unlicensed freedom of the reader, and of the book as the most potent means of “resistance of meaning to mortality” (G. Steiner).